Selective catalytic reduction of NOx with ammonia (NH3-SCR) over copper loaded LEV type zeolites synthesized with different templates. Issue 25 (16th June 2022) - Hoffmann, Andreas; De Prins, Michiel; Sree, Sreeprasanth Pulinthanathu; Vanbutsele, Gina; Smet, Sam; Chandran, C. Vinod; Radhakrishnan, Sambhu; Breynaert, Eric; Martens, Johan A.
Abstract : The catalytic activity of LEV type zeolites in NH3 -SCR was dependent on preferential Al siting in the double 6-rings, which in turn was influenced by the choice of structure-directing agent used in the zeolite synthesis. Abstract : LEV type zeolites were synthesized with four different structure-directing agents and converted to copper loaded NH3 -SCR catalysts. The synthesis recipe was found to impact the respective Al population in the two topologically different framework sites in double and single 6-rings, resolvable by 27 Al MAS NMR spectroscopy. Hydrothermal stability was found to be related to the silanol concentration, Si/Al ratio, particle size, crystal morphology, crystal defects, external surface area, and microporosity. Catalytic activity in NH3 -SCR was dependent on preferential Al siting in the double 6-rings. Levinite synthesized using adamantylamine showed the strongest preference for Al atoms sitting in double 6-ring sites, and showed the highest catalytic turnover frequency. Unfortunately, because of the large crystal size, copper loading of this sample was limited to 0.6 wt% while other samples could be loaded with copper up to 3.3 wt%. An optimum combination of hydrothermal stability and catalytic activity was obtained with N, N ′-bis-dimethylpentanediyldiammonium dibromide as structure-directing agent.